Developing Evaluation Criteria of Academicians' Teaching Performance: Discriminant and Logistic Regression Applications - (:unkn) unknown (My University, 2004)
Marmara Üniversitesi İİBF İngilizce İşletme bölümü 1997'den bu yana öğretim üyelerinin performanslarını değerlendirmek amacıyla öğren-cilerine ders değerlendirme anketi uygulanmaktadır. Bu çalışmada 2000-2001 ve 2001-2002 Eğitim ve Öğretim yılında yapılmış anketlerden elde edilen verilere diskriminant ve lojistik regresyon analizleri uygulanmış ve bu analizlerin sonucunda öğrencilerin bakış açıları esas alınarak öğretim üyesi performans değerlendirme kriterleri belirlenmiştir. Araştırma sonucunda hem diskriminant hem de lojistik regresyon metodunda benzer bulgular elde edilmiştir. Her iki analiz bulguları da "öğrencinin dersin işlenişinden memnun olması"nı yeterli ve yetersiz performansı ayırt edici en önemli unsur olarak göstermektedir. Bunu, "öğretim üyesinin konusuna hakim olması" ve "dersin sınavının iyi bir ölçüt" olması takip etmektedir.

Since 1997 students' course evaluation questionnaire (SCEQ) have been conducted in Business Administration Department of Marmara University to evalute teaching effectiveness of instructors. In this study data obtained from 2000-2001 and 2001-2002 questionnaires are used to conduct discriminant and logistic regression analysis. As a result of these analyses evaluation criteria of academicians' teaching performance are developed Findings of both the disciriminant and logistic regression methods show similar results. In both methods "satisfaction with the way course is conducted" is the most powerful item that discriminates effective instructors from ineffective instructors. This item is followed by "instructors being competent in his/her field" and "exams being a good measuring devise".